Modelo de Fisher-Kolmogorov em dinâmica populacional com capacidade de suporte espacialmente dependente - Carvalho, P. G. S de [UNESP] (2003)
We study the spatial and temporal dynamics of a biological population by means of the Fisher-Kolmogorov equation, taking into account a logistic growth and a fickian diffusion. Special attention is payed to the case where the matrix where the population evolves is spatially heterogeneoous, being formed of more favorable and less favorable regions. We generalize the classical results of Skellam for the minimal patch size of a region in order to allow for the survival of a given population, discussing also the importance of the effects of isolation. The results are applyed to the the dynamics of understorey birds in fragments of the Amazonian forest, giving a coherent interpretation for the effects observed at by the PDBFF